On the conception of the creative in natural science and philosophical reflections thereof - Stasiulis, Nerijus (Creativity Studies, 2016)
The article discusses creativity as an ontological principle as it is presented in scientific-philosophical attitudes of a Nobel Prize winner for chemistry Ilya Prigogine and Werner Heisenberg’s pupil and a former director of the Max Planck Institute for Physics Hans-Peter Dürr. These attitudes are assessed in the light of Heideggerian notions of Being, subiectum, ousia and time and thus they themselves shed light on the potentiality of Heideggerian mode of thinking on the conception of the creative in the postmodern society and science. Bergsonian notion of creativity is also invoked. It is presented as a philosophical basis of the postmodern techno-scientific creativity and is discussed in terms of Heideggerian ecstatic temporality. The juxtaposition of the notions presented by Henri Bergson and Martin Heidegger provides the clue to compare and assess the science-based attitudes of Prigogine and Dürr. First published online: 13 Dec 2015